Epstein–Barr virus-associated inflammatory polyp of the proximal cervical trachea causing central airway obstruction: a case report - Ziran Lei; Ning Zheng; Linlin Wang; Ling Fang; Xiang Wu (Frontiers in Medicine, 2026)
Background Intraluminal lesions of the central airway can cause severe obstruction and are usually malignant. Epstein–Barr virus (EBV)-associated inflammatory tracheal polyps are extremely rare and may mimic airway tumors or EBV-associated lymphoproliferative disorders. Case presentation A 35-year-old woman presented with progressive dyspnea and wheezing for 1 month. Contrast-enhanced chest computed tomography and bronchoscopy revealed a solitary intraluminal polypoid lesion arising from the left anterior wall of the proximal cervical trachea, without true subglottic involvement. The lesion extended from approximately 26.3 mm to 40.8 mm caudal to the vocal cords, with a craniocaudal length of approximately 14.5 mm. The minimum residual airway diameter at the narrowest point was approximately 1.7 mm, and the estimated luminal obstruction was approximately 54%. Emergency rigid bronchoscopic cryoresection and cryotherapy were performed, resulting in rapid symptom relief. Histopathology showed polypoid tissue fragments from the proximal cervical trachea with reactive lymphoid hyperplasia beneath the squamous epithelium. Immunohistochemistry supported a reactive process, with no evidence of lymphoma or malignancy. EBER in situ hybridization was positive in a subset of lymphocytes. Tissue-based targeted next-generation sequencing detected abundant EBV sequences, which were confirmed by PCR and Sanger sequencing. The final diagnosis was EBV-associated inflammatory polyp of the proximal cervical trachea. Conclusions EBV-associated inflammatory tracheal polyps may present as life-threatening airway obstruction. For rare airway lesions with reactive hyperplasia and EBER positivity, integrated histopathological, immunohistochemical, in situ hybridization, and molecular analyses are important to avoid misdiagnosis. Bronchoscopic intervention can effectively relieve obstruction, but follow-up is needed to monitor recurrence and airway stenosis.